How in constitutional protection, the right to a healthy environment can be guaranteed - Delia Samaniego-Quiguiri, Diego Bonilla-Morejón, Carlos Bucheli-Espinoza,; Franklin Murillo Ramos, Ítalo Gaibor-Yánez, Fabian Toscano Broncano, (Opción)
In this essay, it dates from an analysis of the Constitutional Amparo to guarantee the right to a healthy environment, how and when the constitutional guarantees must be filed, their usefulness, additionally it is made known in a synthetic way, the different analyzes carried out by the Constitutional Court, when it becomes aware that constitutional rights and precepts have been violated. The Constitutional Guarantee on this occasion is focused as a guarantee of the right to a healthy environment, because the conditions have changed as we have evolved, from international law when we talk about human rights, until it has been included in the constitutions of the different countries.